Information Sharing with Uncertain Consumer Preferences for Store Brands - Yu Ning; Yang Tong; Jicai Li (Journal of Theoretical and Applied Electronic Commerce Research, 2025)
Information asymmetry between manufacturers and online retailers regarding consumer preferences for store brands profoundly influences operational strategy. By leveraging information technology, online retailers can collect valuable consumer data, creating a strategic dilemma: whether to share this information with manufacturers and, if so, with which manufacturer (national or third-party). This study aims to explore an online retailer’s strategic decisions regarding sharing information with manufacturers, filling a gap in the literature on store brands and consumer preferences. Using game theory, we analyze the interactions among an online retailer, a national manufacturer, and a third-party manufacturer, incorporating the Hotelling model to capture consumer preference and product differentiation. Our findings reveal that information sharing does not consistently benefit the online retailer or manufacturers. Notably, without side payment, the online retailer is unwilling to share information with either manufacturer, and manufacturers do not always gain more from receiving such information—a result that challenges conventional wisdom. However, when side payment is introduced, the online retailer’s willingness to share information depends on key factors: the probability of low brand loyalty (low-type) consumers, the proportion of comparison shoppers, the side payment, and the degree of information uncertainty. These findings provide innovative insights for operations managers, highlighting the critical role of information management in shaping strategic decisions and enhancing the efficacy and financial outcomes of information sharing in the context of store brands.